Article 55 on Open-Price Contract: A Wider Interpretation Necessary? - Amalina Ahmad Tajudin (Journal of Arts & Humanities, publisher, 2024)
This article analyses open-price mechanism under the United Nations Convention on Contracts for the International Sale of Goods (CISG) 1980. It proposes for a wider interpretation of Article 55 of the CISG. Currently, the CISG compromises to the preference of its Member States by allowing contracting parties a choice; either to fix price, or to leave price open in a contract of sale. Such option under the CISG is seen under two distinguished provisions, whereby contracting parties may choose to be bound either by a fixed-price term in Article 14(1), or by an open-price term under Article 55. While open-price mechanism could protect the validity of long-term business dealings, the CISG courts tend to validate open-price term dealings under Article 55 subject to the fulfilment of Article 14(1). Hence a more flexible interpretation of Article 55 of the CISG could be given since the current interpretation does not actually allow a workable open-price mechanism in times of rapid price changes. In the spirit of upholding friendly international business, this article suggests that not only both provisions should be interpreted separately, but also the scope of Article 55 could be extended to cover more cases of open-price contracts affected by market price changes.Keywords: CISG, Open price, Article 14, Article 55, sale of goods